2020
DOI: 10.15405/epsbs.2020.01.14
|View full text |Cite
|
Sign up to set email alerts
|

"Criteria For Teaching Quality And Learning Quality (Inclusive Education In Russian Universities)"

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In determining the criteria for monitoring the quality of teaching and learning in inclusion as a whole and creating the digital profile for monitoring the quality of teaching for hearing impaired students, in particular, the research group Serebryakova, Krasavina, Ponomarenko, and Zhuykova (2019) We identified two special features of the technique: 1) it is used to train personnel for the digital economy (mainly multi-skilled programmers, i.e. mostly talented and creative students with excellent academic background, and 2) so far, in Federal universities this technology is not leading but only supplements the conventional one, approved by Federal Standards.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In determining the criteria for monitoring the quality of teaching and learning in inclusion as a whole and creating the digital profile for monitoring the quality of teaching for hearing impaired students, in particular, the research group Serebryakova, Krasavina, Ponomarenko, and Zhuykova (2019) We identified two special features of the technique: 1) it is used to train personnel for the digital economy (mainly multi-skilled programmers, i.e. mostly talented and creative students with excellent academic background, and 2) so far, in Federal universities this technology is not leading but only supplements the conventional one, approved by Federal Standards.…”
Section: Literature Reviewmentioning
confidence: 99%